Constructing Social Relation Models in Multicultural Societies Through Coffee Table Books to Strengthen Pluralism - Abd Mu’id Aris Shofa; Muhammad Mujtaba Habibi; Alfian Fawaidil Wafa; Hanafi Hanafi; Hafidah Putri Pangestu (Eastasouth Institute, 2026)
This research aims to construct a model of social relations of multicultural communities in Sidodadi Village, Gedangan, Malang Regency, which is known as a religious moderation village. The approach used is qualitative with phenomenological methods, data collection through interviews, observation and documentation, which is then analyzed through the stages of collection, condensation, data presentation, and drawing conclusions. The results of the study show that the social relations model in Sidodadi Village was formed through the integration of three Pierre Bourdieu theories, namely: 1) habitus, which is internalized from an early age through the example of religious leaders; 2) capital, based on mutual trust implemented by the location of places of worship in close proximity; and 3) arena, the existence of an inclusive arena in community activities that ensures equality without domination. This is influenced by internal factors (local actors), infrastructure and the existence of a tradition of mutual cooperation. This social relations model is constructed into visual communication media in the form of a coffee table book, which functions strategically as a practical, aesthetic, and persuasive instrument to educate the public about the value of pluralism as well as an alternative strategy for preventing intolerance in an inclusive manner.